Futıle Treatment and Effects on Intensıve Care Nursing - Mahinur Durmuş İskender (LookUs Bilisim A.S., 2018)
Entering high technology involves not only the recovery of the disease in progressive or terminal illness, but also the provision of postponement of death and other options for the end of life. Especially in critical care units where critical care is provided, the availability of technology leads to increased use of technological intervention methods. This situation reveals useless perception of the attempts made to the patient in terms of patients and their relatives as well as healthcare providers and the concept of futile treatment, which is an important problem in the decisions regarding the end of life. The concept of futile treatment is used for treatments that are more expensive or more risky if the patients are unlikely to be able to correct the situation or are less likely to be more beneficial than currently available treatment. While the progress of the disease progression is a reward for the nurses, it can cause the care, stress and frustration to extend the life of the patient only. Continuing the treatment that nurses think is useless can cause moral distress, compassion fatigue and burnout in nurses over time. The effect of the useless careless treatment on the nurses will be included in the literature.
Keywords: moral distress; futile treatment; burnout; compassion fatigue; R; Medicine; 3. Good health